2022
DOI: 10.3389/fcimb.2021.795333
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Induced Modulation of Gram-Positive Gut Bacteria and Metabolites Remediates Insulin Resistance in iNOS Knockout Mice

Abstract: The role of oxidative and nitrosative stress has been implied in both physiology and pathophysiology of metabolic disorders. Inducible nitric oxide synthase (iNOS) has emerged as a crucial regulator of host metabolism and gut microbiota activity. The present study examines the role of the gut microbiome in determining host metabolic functions in the absence of iNOS. Insulin-resistant and dyslipidemic iNOS−/− mice displayed reduced microbial diversity, with a higher relative abundance of Allobaculum and Bifidob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…This may explain the rise in Fusobacteriota , an anaerobic group, in the absence of iNOS. Additionally, the upregulation of inflammatory markers in our transcriptomic analysis signifies that iNOS deficiency alters the immune environment, potentially impacting the gut’s ability to manage its microbiota [ 10 ]. Previous studies have shown that Aeromonas presence can significantly upregulate the host iNOS gene expression [ 40 ], and iNOS knockout zebrafish have displayed an increased Aeromonas presence, reinforcing NO’s role in the intestinal barrier and the antimicrobial function [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the rise in Fusobacteriota , an anaerobic group, in the absence of iNOS. Additionally, the upregulation of inflammatory markers in our transcriptomic analysis signifies that iNOS deficiency alters the immune environment, potentially impacting the gut’s ability to manage its microbiota [ 10 ]. Previous studies have shown that Aeromonas presence can significantly upregulate the host iNOS gene expression [ 40 ], and iNOS knockout zebrafish have displayed an increased Aeromonas presence, reinforcing NO’s role in the intestinal barrier and the antimicrobial function [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of gut integrity, NO’s contribution is observed through its regulation of mucosal perfusion, smooth muscle relaxation, and epithelial secretory functions, collectively influencing the gut microbiota’s composition and homeostatic balance [ 7 , 8 ]. Mammalian model research has elucidated that perturbations in NOS expression can precipitate marked alterations in gut microbial consortia, consequentially affecting immune reactivity and disease susceptibility, with conditions such as inflammatory bowel syndrome and adiposity being among the notable outcomes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mice were then sacrificed and analyzed on Day 3 after the last caerulein injection by a lethal dose of pentobarbital sodium. For the differentially targeted commensal bacterial disruption experiment, the mice were treated with broad-spectrum ABX (0.5 g/L vancomycin, 1 g/L neomycin, 1 g/L ampicillin, and 1 g/L metronidazole) 16 , G + ABX (0.5 g/L vancomycin) 17 or G – ABX (1 g/L neomycin) 18 . The mice were given antibiotics (200 μL/mouse) daily by gavage from a week before the caerulein injection to the sacrificed day.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic mice were found to have severely dysregulated intestinal flora in the early days of life, and treatment with the insulin receptor antagonist S961 increased the intestinal permeability and disrupted the integrity of the intestinal barrier [75]. In addition, microbial diversity was reduced in IR iNOS -/mice, while the abundance of Haemophilus and Bifidobacterium and Gram-positive bacteria was increased, which was accompanied with alteration in serum metabolites and metabolic dysregulation [76]. Some researchers found that there was a correlation between IR, gut flora and A␤ formation or deposition.…”
Section: Intestinal Dysbiosis Induces Ir To Exacerbate Aβ Depositionmentioning
confidence: 99%